PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP KESTABILAN EMOSI WARGA BINAAN REMAJA - Eva Novianti Tanjung Tanjung; Fadhilla Yusri; Yuliana Nelisma (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This research is motivated by the phenomena found in Class II A prison in Sibolga which shows that inmates still have low emotional stability displayed by teenagers, such as being easily provoked by ridicule given by friends, and causing fights. Researchers are more focused on youth assisted residents in Class II A Sibolga Lapas. To increase the emotional stability of the assisted adolescents, one of the services in guidance and counseling is group guidance, which aims for researchers to find out the effect of group guidance services on the emotional stability of Class II A Sibolga prison residents. This study belongs to the Pre-Experimental Model One Group Pretest and Posttest Design. The population in this study were 26 residents of Barus Prison. The technique used in sampling was the Non-Random Sampling technique, namely Purposive Sampling where sampling was taken based on certain considerations, the samples were Youth Assisted Residents of Class II A Sibolga Prison who were indicated to have low emotional stability, namely 9 inmates. The data collection instrument was the Likert Scale, data analysis used a non-parametric statistical test with the Wilcoxon signed rank test with the help of (SPSS) 24. The results show that the value of the Z test (Wilcoxon) shows the difference between pretest and posttest. The results of Wilcoxon calculations for the Z table value are -2.675b. based on the applicable provisions the Wilcoxon test results sig p value of 0.007 < α (α = 0.05) which means that Ha is accepted and Ho is rejected. From the results of the Wilcoxon test calculations, it can be concluded that there is an increase in emotional stability after being given group guidance services.